2022
DOI: 10.1089/can.2021.0093
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol for COVID-19 Patients with Mild to Moderate Symptoms (CANDIDATE Study): A Randomized, Double-Blind, Placebo-Controlled Clinical Trial

Abstract: Importance: Owing to its anti-inflammatory properties and antiviral ''in vitro'' effect against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), cannabidiol (CBD) has been proposed as a potential treatment for coronavirus disease 2019 . Objective: To investigate the safety and efficacy of CBD for treating patients with mild to moderate COVID-19. Design: Randomized, parallel-group, double-blind, placebo-controlled clinical trial conducted between July 7 and October 16, 2020, in two sites in Brazil.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 30 publications
1
15
0
3
Order By: Relevance
“…However, only two reports have been conducted on humans. One of the studies reported that CBD administration in COVID-19 patients failed to prevent the deterioration of the clinical status of COVID-19 symptoms [ 50 ], whereas the other study reported that CBD administration in healthcare workers during the COVID-19 pandemic could reduce the symptoms of burnout and emotional exhaustion [ 51 ]. This means that there is no evidence that CBD can prevent or reduce SARS-CoV-2 infection or severity in human studies, but it might be effective for reducing pandemic-related stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, only two reports have been conducted on humans. One of the studies reported that CBD administration in COVID-19 patients failed to prevent the deterioration of the clinical status of COVID-19 symptoms [ 50 ], whereas the other study reported that CBD administration in healthcare workers during the COVID-19 pandemic could reduce the symptoms of burnout and emotional exhaustion [ 51 ]. This means that there is no evidence that CBD can prevent or reduce SARS-CoV-2 infection or severity in human studies, but it might be effective for reducing pandemic-related stress.…”
Section: Discussionmentioning
confidence: 99%
“…Phytocannabinoids might indirectly relieve the disease progress of COVID-19 patients through their anti-inflammatory properties [266]. However, CBD failed to alter the clinical disease development of COVID-19 when given at a daily dose of 300 mg for 14 days [267]. Additionally, caution should be taken into account due to the immunosuppressive activities of phytocannabinoids that can prevent proper anti-viral immune responses [268].…”
Section: Anti-viral Activities Of Phytocannabinoidsmentioning
confidence: 99%
“…( Kayser, et al, 2020 ; Lawn, et al, 2020 ; Bebee, et al, 2021 ; Bonn-Miller, et al, 2021 ; Crippa, et al, 2021 )…”
Section: Resultsunclassified